2017
DOI: 10.1007/s00420-017-1257-4
|View full text |Cite
|
Sign up to set email alerts
|

The Gulf oil spill, miscarriage, and infertility: the GROWH study

Abstract: The oil spill appears to have affected reproductive decision-making. The evidence is not strong that exposure to the oil spill was associated with miscarriage or infertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Other limitations of the study include the fact that the post-oil spill and pre- and post-samples are different, most obviously by conditioning on gravidity, and the age and gravidity at a second pregnancy is by definition larger than at the first. Thus, the earlier pregnancies are an imperfect control and residual confounding is possible, although previous analysis of ours found no association between oil spill exposure and fertility [ 46 ]. Similarly, oil spill exposure is self-reported, which likely leads to misclassification or, at least, inexactness in measurement; the most likely consequence of this is bias towards the null.…”
Section: Discussionmentioning
confidence: 81%
“…Other limitations of the study include the fact that the post-oil spill and pre- and post-samples are different, most obviously by conditioning on gravidity, and the age and gravidity at a second pregnancy is by definition larger than at the first. Thus, the earlier pregnancies are an imperfect control and residual confounding is possible, although previous analysis of ours found no association between oil spill exposure and fertility [ 46 ]. Similarly, oil spill exposure is self-reported, which likely leads to misclassification or, at least, inexactness in measurement; the most likely consequence of this is bias towards the null.…”
Section: Discussionmentioning
confidence: 81%
“…1620 women filled out at least 1 questionnaire or interview, including 443 women who were pregnant at the time of the interview. Blood and saliva samples were additionally requested [ 33 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, pregnant women who lived near the Hebei Spirit spill site in South Korea reported more eye irritation, headaches, and pain than those further away (B.-M. Kim et al, 2009). With regard to reproductive health, Harville et al (2018) found little evidence of DWH spill exposure being associated with increased miscarriages or infertility in women from southeastern Louisiana, although spills in Nigeria have been linked with increased mortality rates among newborn children (Bruederle and Hodler, 2019). Among patients (predominantly African American women) seeking care at a Federally Qualified Health Center in an underserved area affected by DWH, post-traumatic stress disorder was associated with headaches, chest pains, dizziness, or trouble sleeping (Langhinrichsen-Rohling et al, 2017).…”
Section: Women Pregnant Women and Childrenmentioning
confidence: 99%